Preservice teachers' preparedness to serve different family compositions. Issue 4 (2nd October 2019) - Miller, Kyle
ABSTRACT: This study explored preservice teachers' (PSTs) perceived competencies and weaknesses in regard to working with a diverse range of students' families, as well as what contributes to their level of preparedness to serve different family types. A sample of 25 Elementary Education PSTs completed surveys and participated in interviews related to their family-related coursework and experiences, memories of home-school connections, and future plans to connect with students' families. Numeric frequencies of responses showed that PSTs felt the most prepared to serve traditional ('nuclear') families and the least prepared to serve divorced, single and same-sex parents. A thematic analysis revealed a contrast between participants who simply desired to serve and those who felt ready to serve different family types. Participants also rejected the notion of a 'normal' family, while simultaneously using heteronormative language when discussing different family types. The article offers implications for teacher educators.